Human Resource Management for Qur’anic Literacy in Digital Primary Education - Maskin Maskin; Ahmad Zainuri; Fitri Oviyanti; Saipul Annur (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
This study examines the strategic role of Human Resource Management (HRM) in enhancing Qur’anic literacy in digital-age primary education. Despite widespread digital access, students’ Qur’anic reading proficiency remains limited, indicating a gap between technological availability and instructional practices. This research employs a qualitative case study design, involving a principal, teachers, and parents through observation, interviews, and document analysis. The findings reveal that HRM functions as a central mechanism linking digital resources and learning outcomes through planning, implementation, and evaluation. However, the absence of structured training, institutional policies, and digital assessment systems limits sustainability. The present research proposes an integrative HRM–digital learning framework, positioning HRM as a mediating system connecting teacher competence, digital infrastructure, and learning outcomes. The findings contribute theoretically to Islamic education management and offer practical implications for policy and school leadership.